Keys to the Sciences : Maqālīd al-ʿulūm. A Gift for the Muzaffarid Shāh Shujāʿ on the Definitions of Technical Terms - Dadkhah, Gholamreza,; Pourjavady, Reza, (Islamic Philosophy, Theology and Science. Texts and Studies;, 2020)
Maqālīd al-ʿulūm (Keys to the Sciences) is a significant source on definitions of Arabic scientific terms in the post-classical period. Composed by an anonymous author, it contains over eighteen hundred definitions in the realm of twenty-one religious, literary, and rational sciences. The work was dedicated to the Muzaffarid Shāh Shujāʿ, who ruled over Shiraz and its neighbouring regions from 759/1358 to 786/1384. The present volume contains a critical edition of Maqālīd al-ʿulūm based on its three extant manuscripts. In the introduction, the editors review previous scholarship on the text, present an overview of patronage at the court of Shāh Shujāʿ and identify some of the sources used by the author of the work. They suggest that the work in its structure mirrors Abū ʿAbdullāh Khwārazmī's Mafātīḥ al-ʿulūm, completed in 366/976.